Annual Report on Exchange Arrangements and Exchange Restrictions 1983. (Annual Report on Exchange Arrangements and Exchange Restrictions, 1983)
This paper highlights information available to the IMF from a number of sources, including that provided in the course of consultation visits to member countries, and it has been prepared in close collaboration with national authorities. Measures intensifying members' trade restrictions are subject to similar reporting provisions when a member has been granted an arrangement for the use of the IMF's resources. The report centers on exchange arrangements and exchange restrictions, but it is also more comprehensive in that it presents other external economic policy measures and intergovernmental arrangements that may have balance of payments implications. As in previous reports, questions of definition and jurisdiction have not been raised; the description in the report of a restrictive practice by a member does not imply that it is or is not being maintained consistently with the IMF's Articles, or that, if subject to Article VIII, it has or has not been approved by the IMF.